Predictive value of left ventricular myocardial strain by four‐dimensional speckle tracking echocardiography combined with red cell distribution width in heart failure with preserved ejection fraction. Issue 6 (4th June 2019) - Fang, Sihua; Zhang, Zhihua; Wang, Ying; Jiang, Fan; Yang, Kai; He, Fei; Zhang, Chaoxue
Abstract: Objectives: The diagnostic difficulty of heart failure with preserved ejection fraction (HFpEF) is differentiating it in patients with similar symptoms and signs. This study aimed to assess the potential predictive value of left ventricular global longitudinal strain (GLS), global radial strain (GRS), global circumferential strain (GCS), and global area strain (GAS) measured by four‐dimensional speckle tracking echocardiography (4DSTE) combined with red cell distribution width (RDW) in patients with HFpEF. Methods: One hundred and sixty‐nine patients with symptoms or signs indicative of chronic heart failure and a left ventricular ejection fraction (LVEF) ≥ 50% and fifty controls with normal LVEF were recruited in this study. Standard echocardiography and 4DSTE examinations were performed. Laboratory examinations including RDW were performed on the same day as the echocardiographic study. Results: GLS, GCS, GRS, and GAS in the patient cohort were significantly lower, and RDW was significantly higher than those in the control cohort ( P  <   0.01), and the strain parameters in definite HFpEF patients were also dramatically lower than the rest patients ( P  <   0.01). The associations of age, gender, NYHA classification, hypertension history, left ventricular end‐diastolic volume index, interventricular septal thickness, and diastolic dysfunction with HFpEF were significantly improved by adding 4DSTE parameters ( P  <   0.01) and further improved by adding RDW ( P  <   0.01). Conclusions: In suspected HFpEF patients, who have symptoms or signs of heart failure, even without other conventional evidence of this diagnosis, GLS, GRS, and GCS have potential independent predictive value, while RDW has independent incremental predictive value for HFpEF.